2010
DOI: 10.3389/fpsyt.2010.00017
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial findings in alcohol-dependent patients before and after three months of total alcohol abstinence

Abstract: Alcohol use disorders (AUDs) may be associated with several psychological and affective disorders. It is controversial, however, if these symptoms are a cause or rather a consequence of alcohol dependence. There are few data testing simultaneously psychosocial and affective disorders before and after a period of alcohol abstinence. The aim of this study was to perform multiple psychometric evaluations in alcohol-dependent patients before and after 12 weeks of abstinence. Twenty-five alcohol-dependent patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It was suggested that patients with SUD experience anger more often than others, are more likely to express anger towards other persons or objects in the environment, and have less control over their angry feelings 66 , particularly in terms of intoxicated (chemical) aggression [67][68][69] . Thus, while substance use alleviates chronic anxiety temporarily 70 , it can trigger verbal or physical aggression chemically 71 . Consistent with this finding, total abstinence from substance improves aggressiveness 72 , and the treatment of substance dependency may be an important target for prevention of aggressive behaviors 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that patients with SUD experience anger more often than others, are more likely to express anger towards other persons or objects in the environment, and have less control over their angry feelings 66 , particularly in terms of intoxicated (chemical) aggression [67][68][69] . Thus, while substance use alleviates chronic anxiety temporarily 70 , it can trigger verbal or physical aggression chemically 71 . Consistent with this finding, total abstinence from substance improves aggressiveness 72 , and the treatment of substance dependency may be an important target for prevention of aggressive behaviors 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The above instruments have already been used in the study of disability across a number of sociodemographic variables and different diseases and disorders, including acne vulgaris with social phobia [ 36 ], bipolar disorder [ 37 - 39 ], undifferentiated peripheral inflammatory arthritis [ 40 ], adult-onset hearing loss [ 41 ], psychotic disorders [ 42 - 47 ], multiple sclerosis [ 47 ], depression and anxiety [ 7 , 46 , 48 - 60 ], injury [ 61 - 63 ], alcohol abuse [ 64 ], sex differences [ 53 , 65 - 67 ], arthritis [ 60 ], chronic spinal pain [ 60 ], high blood pressure [ 60 ], social anxiety [ 68 ], obsessive-compulsive disorder [ 69 ], on-pump coronary artery bypass [ 70 ], dementia [ 71 ], cancer with pain [ 72 , 73 ], obesity and type 2 diabetes mellitus [ 74 ], mental-physical disorders comorbidity [ 75 , 76 ], leprosy [ 77 ], ADHD [ 78 , 79 ], anxiety in children [ 80 ], Parkinson’s disease [ 81 ], macular degeneration [ 48 ], inflammatory arthritis [ 23 ], migraine [ 8 ] and systemic sclerosis [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%